Author Correction: Pathogen-derived HLA-E bound epitopes reveal broad primary anchor pocket tolerability and conformationally malleable peptide binding. Issue 1 (December 2018) - Walters, Lucy; Harlos, Karl; Brackenridge, Simon; Rozbesky, Daniel; Barrett, Jordan; Jain, Vitul; Walter, Thomas; O'Callaghan, Chris; Borrow, Persephone; Toebes, Mireille; Hansen, Scott; Sacha, Jonah B.; et al.
The original version of this Article contained an error in the spelling of the author Jonah B Sacha, which was incorrectly given as Jonah Sacha. These errors have now been corrected in both the PDF and HTML versions of the Article.